Antioxidant Activity Sonneratia caseolaris Leaves Extract at Different Maturity Stages - Winarti Winarti; Boedi Setya Rahardja; Sudarno sudarno (Universitas Airlangga, 2019)
Free radical is a reactive component because it has one or more electrons. Free radical is very dangerous for our body because it can cause degenerative diseases, such as cancer, heart attack, and aging. Cancer and heart attack are one of the most killer disease. All we can do to decrease the free radical effect is consume antioxidant. S. caseolaris leaves has antioxidant activity, but it has known yet which stage of maturity is the best one for produce the highest antioxidant activity. This purpose of this research is knowing the influence between maturity and antioxidant activity at different maturity stages. This method of this research is experimental with Completely Randomized Design. The treatment in this research is vitamin C, fresh leaves in ethanol 96% extract, young leaves in ethanol 96% extract, and mature leaves in ethanol 96% extract. The main parameter of this research is IC50 values and the secondary parameters are total content of phytochemical in every extract. Data analysis using descriptive method with 4 treatments and five replications. The result of this research show that the maturity has influence in antioxidant activity. Inhibitory concentration 50 (IC50) values of shoot leaves extract, young leaves extract and mature leaves extract is 12.0013 ppm, 13.9915 ppm and 14.6613 ppm. All of them are called antioxidant which has very strong activities. The highest phytochemical compound is found on shoot leaves extract with ethanol 96% solvent.